Carta de C. Domínguez a Roberto H. Todd - Todd, Roberto H.; Domínguez, C. (My University, 1935)
Recolecta a favor de los herederos del Lcdo. Martínez Dávila.
Keywords: Martínez Dávila, Manuel A.,1883-1934